2021
DOI: 10.3390/jmse9080834
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Wave-Induced Stokes Transport Effects on Sea Surface Temperature Simulations in the Western Pacific Ocean

Abstract: This study investigated the performance of two ocean wave models, that is, Simulation Wave Nearshore (SWAN) and WAVEWATCH-III (WW3), and the interannual and seasonal variability of transport induced by Stokes drift during the period from 1989 to 2019. Three types of sea surface wind products were used for wave simulation: the European Centre for Medium-Range Weather Forecasts (ECMWF) Interim, the Cross Calibrated Multi-Platform Version 2.0 (CCMP V2.0) from Remote Sensing Systems (RSS), and the National Centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…It was found that the accuracy of the water temperature was improved by including the four wave-induced terms, especially for the high WW3-simulated SWH in July and September. As mentioned in [9], wave-induced Stokes transport in the China Seas gradually increased between 1987 and 2020. The term of wave should be included in the SST simulation by sbPOM at specific regions, e.g., the Arctic Ocean [5] and China Seas, and at extreme events, e.g., typhoon and hurricane.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It was found that the accuracy of the water temperature was improved by including the four wave-induced terms, especially for the high WW3-simulated SWH in July and September. As mentioned in [9], wave-induced Stokes transport in the China Seas gradually increased between 1987 and 2020. The term of wave should be included in the SST simulation by sbPOM at specific regions, e.g., the Arctic Ocean [5] and China Seas, and at extreme events, e.g., typhoon and hurricane.…”
Section: Discussionmentioning
confidence: 84%
“…The characteristics of ocean dynamics are complicated in the open sea areas of the Antarctic Ocean, e.g., the circumpolar current [7] and huge swells [8]. In fact, both the currents and waves play important roles in water temperature [9], especially under the high sea state in the Antarctic Ocean. However, regarding the oceanography research conducted on the Antarctic Ocean, the characteristics of the atmospheric-marine dynamics and climate change, i.e., wind [10], waves [11], and currents [12], have been individually studied.…”
Section: Introductionmentioning
confidence: 99%
“…This obviously ignores potential interactions among different factors, such as wind speed, sea surface temperature, and salinity, which may have indirect effects on the CO 2 partial pressure at the surface. Several studies have also provided evidence that changes in SST, SSS, and wind speed can induce variations in the partial pressure of CO 2 via physicochemical processes that affect CO 2 exchange (Kashef-Haghighi and Ghoshal, 2013;Sun et al, 2021a;Sun et al, 2021b;Wanninkhof, 1992). We hope that necessary groundwork can be performed to address these problems in future research.…”
Section: Discussionmentioning
confidence: 95%
“…In the above data, winds are implemented in two wave numerical models, that is, WAVEWATCH-III (WW3) [30], which was developed by the National Centers for Environmental Prediction (NCEP) of the National Oceanic and Atmospheric Administration (NOAA), and Simulation Wave Nearshore (SWAN) [31], which was developed by the Delft University of Technology. It was revealed in [32] that WW3, using 1 • gridded CCMP winds that are assimilated by ERA-Interim reanalysis winds and observations, had the best performance in wave simulation for the Western Pacific Ocean. However, two aspects of employing those winds must be noted: (1) the inevitable error in the meteorological numerical model and (2) the under-estimation in the TCs [33].…”
Section: Introductionmentioning
confidence: 99%